Randomised controlled trial demonstrating the impact of behaviour change intervention provided by dental professionals to improve gingival health. (December 2021) - Holloway, Jessica A.; Davies, Maria; McCarthy, Claire; Khan, Iftekhar; Claydon, Nicholas C.A.; West, Nicola X.
Abstract: Aims: To determine impact of oral hygiene behaviour change intervention compared to the prevailing standard of oral hygiene advice provided in general dental practice, on bleeding on probing (BOP) in gingivitis patients, over 3-months. The effect of providing power-brushes was also evaluated. Materials and methods: NHS dental practices were cluster-randomised to intervention or control (2:1). Dentists at intervention sites received behaviour modification training. Participants were stratified to high (≥20% BOP) or low (<20% BOP) presence of gingivitis and a subset assigned a power-brush. BOP and plaque scores were assessed at baseline and 3-months. Results: A total of 538 participants (369:169; intervention: control) completed the study. BOP reduced in both gingivitis groups with significantly greater reduction in intervention compared to control group (BOP:38% vs 19%, p = 0.0236); Borderline significance favouring the intervention was demonstrated for the low gingivitis group (BOP:37% vs 15%, p = 0.0523). A highly significant reduction in BOP (intervention vs control) was demonstrated for volunteers who swapped from manual to power-brush (44% vs 37%, p = 0.0039). Plaque score improved more in control than intervention group (Plaque:37% vs 44%, p = 0.00215). Conclusions: Behaviour change techniques were readily mastered by the dental professional researchers. The introduction of an oral hygiene behaviour change intervention significantly reduced gingivitis in volunteer patients compared to control at 3 months. Swapping to a power-brush significantly favoured BOP reduction compared to manual brush continuation although plaque reduction did not follow expectation in comparison to BOP scores. Behaviour change techniques should routinely be considered in patient care. Clinical significance: Plaque-induced gingivitis is highly prevalent in the UK despite being preventable with good oral hygiene. Its continuum, periodontitis, negative impacts quality of life. This study suggests oral hygiene behavioural interventions (GPS) significantly reduce gingivitis and that GPS introduction will improve oral health and may improve quality of life.